Imaging in Esophageal Cancer: A Comprehensive Review - Talasila, Pallavi; Hedge, Swaroop G.; Periasamy, Kannan; Nagaraj, Satish Subbiah; Singh, Harmandeep; Singh, Harjeet; Gupta, Pankaj (Indian Journal of Radiology and Imaging, 2024)
Esophageal cancer is one of the common cancers. Risk factors are well recognized and lead most commonly to two distinct histological subtypes (squamous cell carcinoma and adenocarcinoma). The diagnosis is based on endoscopic evaluation. The most challenging aspect of management is accurate staging as it guides appropriate management. Endoscopic ultrasound, computed tomography (CT), positron emission tomography-CT, and magnetic resonance imaging are the imaging tests employed for the staging. Each imaging test has its own merits and demerits. Imaging is also critical to evaluate posttreatment complication and for response assessment. In this review article, we discuss in detail the risk factors, anatomical aspects, and role of imaging test in staging and evaluation of complications and response after treatment.
Keywords: esophageal cancer; CT; endoscopic ultrasound; imaging; MRI